BENCHMARKING : INDIKATOR KINERJA YANG DIUNGKAPKAN DALAM LAPORAN BERKELANJUTAN (SUSTAINABILITY REPORTING) - Wardi, Jeni (Universitas Lancang Kuning, 2025)
This research to find out how to disclose sustainability reports based on the items in the GRI guidelines and what the level of breadth and depth of disclosure of sustainability reports for case study companies at PT. Unilever, PT Sidomuncul and BCA Syariah, as Benchmarking. The research method used is a qualitative research method, namely a method used to produce data findings without using statistical procedures or measurements. Research Subjects and Objects The research subjects were three companies that had received awards, namely PT. Unilever, PT Sidomuncul and BCA Syariah. Meanwhile, the research object is the Sustainability Reports of the three companies. In general, the results of the analysis of the sustainability reports of the companies Unilever, Sidomuncul and BCA Syariah for 2022 based on GRI Standards show good disclosure, although not all indicators are disclosed by these companies. In 2022, the highest disclosure of Standard GRI indicators will be presented by BCA Syariah. by 33% on General Standards and 40% on Specific Standards. The proportion of CSR program disclosures through Specific Standard indicators including Economic, Environmental and Social Performance indicators during 2022 was carried out by Sidomuncul with a total score of 50, followed by second place namely Unilever with a total score of 34, while the company with the least disclosure was BCA Syariah with total score of 29.